2008
DOI: 10.1177/875512250802400105
|View full text |Cite
|
Sign up to set email alerts
|

Rash and Liver Dysfunction Related to Lamotrigine Therapy

Abstract: An 81-year-old female with a 50 year history of bipolar disorder and no known history of liver dysfunction LEA RC SERWETMAN PharmD, at time of writing, Clinical Rotation in Acute Care, Advanced Pharmacy Experiential Program, Objective: To report a case of rash and liver dysfunction associated with lamotrigine treatment.Case Summary: An 81-year-old woman with a history of bipolar disorder presented to the emergency department with complaints of fever, chills, nausea, and headache. Two weeks prior to presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Many patients showed improvement after stopping AEDs. Furthermore, combined treatment with VPA and LTG was observed to cause hepatotoxicity through decreased clearance of LTG [8,11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many patients showed improvement after stopping AEDs. Furthermore, combined treatment with VPA and LTG was observed to cause hepatotoxicity through decreased clearance of LTG [8,11].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, LTG has rare adverse severe skin reactions such as: Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN), drug rash with eosinophilia and systemic symptoms (DRESS), and anticonvulsant hypersensitivity syndrome, which may lead to terminating LTG treatment [9][10][11]. Slow introduction and titration of LTG dosage may reduce or eliminate these adverse symptoms [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients receiving chronic treatment with LTG in the form of single or polytherapy are at a high risk of elevation of hepatic enzymes without clinical signs or symptoms of hepatic dysfunctions to fatal hepatotoxicity (May et al, 1996;Meshkibaf et al, 2006;Fayad et al, 2000). A study with different dose of LTG showed that at therapeutic level there was a significant increase in the levels of alkaline phosphatase (ALP), aspartate aminotransferase (AST), alanine aminotransferase (ALT), and bilirubin (Serwetman et al, 2008;Overstreat et al, 2002;Moeller 2008;Makin et al, 1995;Sauve et al, 2000).…”
Section: Introductionmentioning
confidence: 99%